Impact of a veterans affairs primary care collaboration to provide remote team‐based care and telehealth introductory pharmacy practice experiences. Issue 9 (26th May 2021) - Carr‐Lopez, Sian M.; Strohecker, Lorrie A.; Miyahara, Randell K.; Patel, Rajul A.; Mai, Yvonne T.; Shek, Allen; Law, Elaine J.
Abstract: Introduction: Developing remote team‐based care and telehealth introductory pharmacy practice experiences (IPPEs) in primary care is desirable. The Department of Veterans Affairs (VA) endorses interdisciplinary teams to provide primary care services for Veterans and utilizes clinical dashboards to support population management. Pharmacy students, during IPPEs, can perform several patient care activities typically done by VA team members. Objective: The primary objective was to describe the economic impact of a collaboration between a VA health care system and a school of pharmacy to provide remote IPPEs. Methods: During Fall 2019, activities of second‐year pharmacy students in a required VA population health IPPE were tracked. Select population management activities typically conducted by nurses, clinical pharmacy specialists (CPS), or primary care providers were assigned to pharmacy students. Students were granted remote access privileges to VA's electronic health record (EHR) and precepted by VA CPS at the university. Students performed prescription drug monitoring program (PDMP) activities, reviewed outside medical records for laboratory results, ordered laboratory tests, conducted telephone pain assessments, and documented progress notes. The average time to complete each function and the average salary for the team member who typically completed the function was used to perform a cost‐benefit analysis. Results: During the semester, 58 students spent 2 hours per week in the IPPE. Students wrote 2118 PDMP progress notes, ordered 1723 laboratory tests for provider signature and sent patients laboratory reminder letters, entered 171 outside laboratory results into VA's EHR, and conducted 183 pain assessments. The semester cost of preceptor salaries was 13 937. Direct benefits to the health system included a salary savings of 24 388.56 to 31 402.03. The net benefit of 10 451.56 to 17 465 resulted in a 75% to 125% return on investment. Conclusion: Identifying practice‐appropriate experiences for pharmacy students enabled active participation in remote team‐based care and telehealth activities, facilitated primary care student experiences, and offered cost savings to the health care system.